The role of Electoral Management Bodies (EMBs) in strengthening democratic participation through elections : a comparative study of Tanzania and Ghana - Fombad, Charles Manga (University of Pretoria, 2025)
Mini Dissertation (LLM (Human Rights and Democratisation in Africa))--University of Pretoria, 2025.